Quality of life among postnatal mothers with normal vaginal delivery and cesarean section in obstetrics & gynaecology clinic, HUSM Kelantan - Shah, Fatin Nur 'Ayuni Mhd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2012)
Childbirth is the following stage for women to be a mother. It affects the mothers' condition in many ways particularly via psychological and physical consequences. Thus, by measuring the quality of life, mothers can gain information on how much change they have gone through following the childbirth process. Increase risk of postnatal morbidity cause a lot of studies done including the role of mode of delivery in post natal mother's condition particularly in life quality. The purpose of this study is to assess the quality of life among postnatal mothers with vaginal delivery and cesarean section. This cross sectional study had 50 respondents who included women aged more than 18, had delivered baby after 4 weeks or above, voluntarily participate in this study and able to speak and understand in Malay and English language. The setting of this study involved 0 & G clinic in HUSM. This study used WHOQoL questionnaire for survey assessment through convenience sampling. This questionnaire also includes sosiodemographic data questionnaire. Statistical analyses used for this study is Independent T test for difference of QoL between NVD and CS mothers, ANOV A test for association of QoL with educational level and socioeconomic status and Pearson Correlation for correlation of QoL with age. Among 50 women participated in this study, 22 were in NVD group while other 28 mothers are in CS group. Based on the results by comparing QoL for NVD and CS mothers, the entire domain except for overview perception towards life, NVD mothers had higher score compared to CS mothers. Even so there is no significance difference of QoL between NVD and CS mothers. In measuring association of QoL with selected socio demographic data which included age, educational level and socioeconomic status, the study showed there is no significance association between QoL with selected socio demographic data. As a conclusion, eventhough the study found no significance difference in QoL and methods of delivery, the higher mean score in NVD mothers compared to CS mothers indicated better improvement in health and recovery process after delivery.